Strategi Penetapan Harga Jual Produk Jajanan di Wisata Kuliner Pasar Bahulak Desa Karungan Kecamatan Plupuh Kabupaten Sragen - widagdo, yohanes martono (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the understanding and skills of culinary business actors in Bahulak Market, Karungan Village, Plupuh District, Sragen Regency, in setting the selling price of snack products in a rational and sustainable manner. The main problem faced by business actors is pricing that is not based on a comprehensive calculation of production costs, resulting in an imbalance between costs and business profits. Through the Asset Based Community Development (ABCD) approach, this activity is designed in the form of training and direct assistance which includes material on the calculation of Cost of Goods Manufactured (HPP), food costs, and simple promotion strategies. The results of the activity showed an increase in participants' knowledge and ability to determine the right selling price, based on raw materials, labour, and the expected profit margin. This service also raises the awareness of business actors to optimise their local assets as community economic strength. With a participatory approach and based on local potential, this activity is expected to become a sustainable model of community-based micro-economic strengthening in the local culinary sector.